Avaliação de Sistemas de Mensagens Instantâneas Móveis (MIM): um estudo sobre o uso do Whatsapp com estudantes do ensino superior - Briskiewicz, Marcos Francisco (2018)
Immediacy related to the exchange of information is a reality faced by the population of modern times and the use of mobile instant messaging (MIM) is indispensable for the communication to happen as expected. Today the majority of the world's population uses MIM systems as a fast and often free medium for the purpose of helping communication in the workplace, exchange of general information and also as a means of entertainment. Due to its importance and effectiveness, several studies seek to understand the factors that determine the adoption and use of these systems. This research aims to evaluate, through the perception of students of higher education, the factors that affect the use of mobile instant messaging services. To achieve this goal, a survey was conducted with 1,386 students from four higher education institutions. After the collection, the modeling of the structural equations was performed using the SmartPLS 2.0 software for the calculation of the partial least squares (PLS), besides the use of the Statistical Package for Social Sciences (SPSS) for the descriptive analysis of the data. This research has as a result that the Quality of Service construct positively influences Confirmation, as well as Confirmation has positive relation with Perceived Utility, Perceived Pleasure, User Interface and Perceived Security. Perceived pleasure and user interface has a positive relationship with satisfaction and the relationship between satisfaction, perceived utility and perceived enjoyment positively influences the intention to use the WhatsApp system. It was identified that, in the context of this research, pleasure and satisfaction act as factors that directly influence the intention to use WhatsApp system, followed by Utility, which makes the use of this system more intuitive than practical.